Bone Mineral Density Accrual Determines Energy Expenditure with Refeeding in Anorexia Nervosa and Supersedes Return of Menses. (23rd August 2011) - Sum, Melissa; Mayer, Laurel; Warren, Michelle P.
Abstract : Osteopenia and osteoporosis are major complications of anorexia nervosa (AN). Since bone is a tissue requiring large amounts of energy, we examined the disproportionate increase in resting energy expenditure (REE) that occurs with refeeding of AN patients to determine if it was related to bone accretion. Thirty-seven AN patients aged23.4 ± 4.8 years underwent a behavioral weight-gain protocol lasting a median of 66 days; 27 remained amenorrheic, and 10 regained menses. Sixteen controls aged25.1 ± 4.7 years were age- and % IBW matched with patients. REE was measured using a respiratory chamber-indirect calorimeter. Significant correlations were found between REE and changes in spine (r = 0.48, P < 0.02 ) and leg (r = 0.43, P < 0.05 ) BMDs in AN patients. Further subgroup analysis of the amenorrheics revealed significant correlation between REE and change in spine BMD (r = 0.59, P < 0.02 ) and higher IGF-1 after weight gain compared to controls. Amenorrheics also had lower BMDs. These findings were absent in the regained menses group. The increase in REE seen in women with AN during nutritional rehabilitation may be related to active bone formation, which is not as prominent when menses have returned.